Two-Dimensional Figure E-Modul with Contextual Teaching and Learning (CTL) Approach - Tri Wahyuningtyas, Dyah; Yuniasih, Nury; Bambang Irawan, Edy; ., Susiswo (International Journal of Engineering and Technology, 2018)
The development of the technology and digital era began with the shift from printed books to electronic books. Therefore, the purpose of this study was to develop a two-dimensional figure module with Contextual Teaching and Learning (CTL) for PGSD students.Â This study applied the Thiagarajan 4D research and development method (Define, Design, Develop, and Disseminate).Â The data analysis techniques used were quantitative and qualitative descriptive data analysis.Â The results of this study were two-dimensional figure e-modules with the CTL approach that can be accessed by PGSD students as geometry teaching materials. The modules are two-dimensional object e-modules with CTL approach validated by experts.Â The results of e-module validation are 90% with highly valid and feasible categories.Â The implementation of e-modules shows an increase in students' understanding of two-dimensional object material.Â